Robust Beamforming Algorithm for Multibeam Satellite Communication Based on Downlink NOMA - Pengcheng KAN; Zining WANG; Huaicong KONG; Jian OUYANG; Min LIN (天地一体化信息网络)
To improved the spectrum efficiency of multibeam satellite system and meet the requirement of multi-access, a robust beamforming and power allocation scheme based on non-orthogonal multiple access (NOMA) was proposed.Under the condition that the imperfect channel state information was known, fi rstly, a power minimization problem subject to probability constraints of users’ quality of service requirement and earth stations’ interference-to-noise ratio was formulated.In order to address the non-convex problem, we then adopted Bernstein inequality to converted the probability constraints into deterministic forms and decomposed the original problem into beamforming sub-problem and power allocation sub-problem, and the robust design was conducted by alternating optimization.Simulation results showed that the proposed scheme has better robustness and eff ectiveness compared with other existing schemes.